2015
DOI: 10.1007/s11302-015-9447-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture on P2X3 receptor regulation in the peripheral and central nervous systems of rats with visceral pain caused by irritable bowel syndrome

Abstract: The aim of this study is to investigate the role of the purinergic receptor P2X 3 in the peripheral and central nervous systems during acupuncture treatment for the visceral pain of irritable bowel syndrome (IBS). A total of 24 8-day-old Sprague-Dawley (SD) neonatal male rats (SPF grade) were stimulated using colorectal distention (CRD) when the rats were awake. The modeling lasted for 2 weeks with one stimulation per day. After 6 weeks, the rats were randomly divided into three groups of eight each: (1) the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…In this study, we found that EA at Zusanli and Shangjuxu (100 Hz for 1.05 s, 2 Hz for 2.85 s alternately, pulse width for 0.1 ms, 1 mA, 30 min/d, once a day) significantly reduced the behavioral AWR score of IBS rats suggesting that EA significantly relieved the visceral hypersensitivity in our IBS rat. It is similar to the effect of EA on visceral hypersensitivity of IBS induced by acetic acid [36], colorectal distension neonatal rat [49], formaldehyde [50], and other injuries previously reported. Previous studies have shown that chemical inflammatory injury to the colon can cause peripheral and central sensitization and increased excitability in neurons [40] and that astrocytes play an important role in the occurrence and maintenance of sensitization [41].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that EA at Zusanli and Shangjuxu (100 Hz for 1.05 s, 2 Hz for 2.85 s alternately, pulse width for 0.1 ms, 1 mA, 30 min/d, once a day) significantly reduced the behavioral AWR score of IBS rats suggesting that EA significantly relieved the visceral hypersensitivity in our IBS rat. It is similar to the effect of EA on visceral hypersensitivity of IBS induced by acetic acid [36], colorectal distension neonatal rat [49], formaldehyde [50], and other injuries previously reported. Previous studies have shown that chemical inflammatory injury to the colon can cause peripheral and central sensitization and increased excitability in neurons [40] and that astrocytes play an important role in the occurrence and maintenance of sensitization [41].…”
Section: Discussionsupporting
confidence: 88%
“…However, the exact mechanism underlying analgesia of EA at low frequency in PDN remains unclear. Previous studies showed that EA had downregulatory effects on PKC and P2X3 receptor in other animal models [26][27][28]. Thus, the present study aimed to investigate the effects of 2-Hz EA on DRG PKC and P2X3 receptor and whether PKC regulates P2X3 receptor, which may be involved in EA analgesia in PDN.…”
Section: Introductionmentioning
confidence: 92%
“…It has been suggested that P2X7R of rat dorsal root ganglia may play a role in the transmission of the nociceptive signal (Liu et al, 2015). Emerging evidence suggests that electroacupuncture may downregulate the expression of the P2X3R and ease the sensitivity to IBS visceral pain (Weng et al, 2015). It may be worth investigating AZD9056 32 in IBS and in related functional gastrointestinal disorders, since the P2X7R antagonist was shown to have some efficacy against chronic abdominal pain in CD (Eser et al, 2015).…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%